A Clinico-Pathological Study on Pleehodara w.s.r. to Splenomegaly and its Comparative Management with Sarapunkha Kshara and Sarapunkha Ghana Vati - Nanda, Riksundar; Panda, Pradip Ku; Nayak, Utkalini; Panda, Sushmirekha; Singh, Vinod Chandra (International Research Journal of Ayurveda & Yoga, 2022)
Introduction- Udara rogas are classified into 8 types according to different Acharyas. Pleehodara is one among them.The main cause behind the development of Udara roga is ‘Mandagni’. In Ayurveda Pleehodara may be correlated with Splenomegaly. Sarapunkha a herbal drug mentioned in Ayurveda classics is effective in Pleehodara. So, a comparative single blind study of Sarapunkha Kshara and Sarapunkha Ghana Vati are taken into consideration for clinical trial for present study. Aims: To study about the comparative clinical efficacy of Sarapunkha Kshara and Sarapunkha Ghana Vati in the management of Pleehodara. Material and Methods- This is a single-blind comparative clinical study with a pre-test and post-test design. The patients were Randomly categorised into two groups.30 patients of Group A(15) and Group-B(15) patients were registered from OPD and IPD of Govt. Ayurvedic College and Hospital, Balangir presented with Subjective parameters and Objective Parameters. After diagnosis they were under trial with Ayurvedic formulations of Sarapunkha Kshara given 500mg twice daily after food in Group A and Sarapunkha Ghana Vati given 2tab (1 tab-500mg) twice daily after food with luke warm water for a period of 30 days respectively. The subjective and objective parameters were assessed in 10 days interval to interpret the result by statistical evaluation. Observation and Results: It had been observed that the result of trial drug Group-A patients was significant (<0.05) to reduce both subjective and objective Parameters after 30 days of treatment as compare to Group-B patients. Conclusion: On comparison between two groups, Sarapunkha Kshara had shown more effect than Sarapunkha Ghan Vati. No adverse effects were noticed during clinical trial in both groups